Pendampingan Online Marketing Kelompok Usaha Zack Kress berbasis Website di Desa Firdaus Serdang Bedagai - Syah, Dedy Husrizal; Harahap, Mukti Hamjah; Lubis, Izwar; Panggabean, Deo Demonta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
To expand marketing reach, this community service aims to develop website-based digital marketing for Zack Krezz MSMEs in Firdaus Village, Serdang Bedagai. The methods used include training and mentoring as well as demonstrations, designing e-commerce websites, and implementing digital marketing strategies by involving the active participation of partners. The results of the community service show an increase in partners' understanding of digital marketing. The e-commerce website was successfully designed and implemented, increasing marketing reach. The main obstacles in the form of limited human resources and internet infrastructure can be overcome through gradual mentoring. Implementing digital marketing has proven effective in increasing the competitiveness of MSMEs in the digital era but requires ongoing mentoring to ensure sustainability. This program can be a model for developing similar MSMEs, with recommendations to expand the scope of digitalization and conduct longitudinal studies to measure long-term impacts